The Public Perception of People's Housing Program (PPR) for Slum Settlement Handling in Malaysia - Yurnal, Yurnal; Saiful Adli, Anis Shafika Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study was to describe public perceptions of people’s housing programs for handling slums in Malaysia. Malaysia has begun organizing and fostering communities that have lived in slums since 1998 in the 'slum-free Malaysia vision 2005' program, and today Malaysia can be said to have successfully resolved slums, through public housing programs. The type of research used is this research is descriptive qualitative, using accidental sampling as sampling technique. Data collection methods used are interview and documentation methods, with research instruments in the form of interview guidelines. The results showed that the community strongly agreed with the existence of The People’s Housing Program (PPR), especially for the lower middle class and poor people in Malaysia. This program is able to realize the dream of the poor to be able to have a place to live that is suitable for living with family. Furthermore, the program itself is acknowledged by the community as being able to deal with slum settlements in Malaysia, and the poor who are biased in occupying slum areas voluntarily move to the houses provided by this PPR. So, people's perception of the Public Housing Program is very supportive especially to deal with slums in Malaysia.